This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
WOW!!
@Ivan Koswara , Consider this. a a a a ⋯ = 2 and a a a a ⋯ = 4 . Both give us a value of a as 2 . But how can a single value of a given us two different answers?
Let the desired quantity be x . Then x = 2 x . By inspection, x = 2 satisfies this equation, so the answer is 0 0 2 .
hey!! 4 also satisfies it!
why answer is not 4??
Log in to reply
I will avoid the rigor here, but basically the function does not grow quickly enough to reach 4.
Let √2^√2^√2... be x, Or √2^x=x Or 2^x=x^2 Or x=2
This can be written as 2 2 1 2 2 1 and it goes on
We can multiply the exponents with each other that leads us to 2 1
Thus, 2 1 = 2
Very, very wrong. ( a b ) c = a ( b c ) . What you have is ( ( ( 2 1 / 2 ) ( 2 1 / 2 ) ) ( 2 1 / 2 ) ) … , which cannot be replaced with ( ( ( ( ( 2 1 / 2 ) 2 ) 1 / 2 ) 2 ) 1 / 2 ) … . Even if you can do that, you will obtain 2 2 1 ⋅ 2 ⋅ 2 1 ⋅ 2 ⋅ … , in which the exponent diverges, not leading to 1 . (It oscillates between 1 and 2 1 .)
Problem Loading...
Note Loading...
Set Loading...
The quantity 2 2 2 … is defined as n → ∞ lim u n of the sequence { u n } satisfying u 1 = 2 , u i + 1 = 2 u i .
These are the steps required:
Claim 1: u i < 2 for all i .
We can do induction on this. The base case, u 1 = 2 < 2 , is correct. Suppose u i < 2 . Since 2 x is increasing (its derivative is always positive), by definition 2 x < 2 y whenever x < y . Thus u i + 1 = 2 u i < 2 2 = 2 , and thus the induction step is proven.
Claim 2: u i + 1 > u i for all i .
For this, we need to prove that 2 x − x > 0 for all x < 2 .
Observe the derivative of 2 x − x ; that is, 2 ln 2 2 x − 1 . When x < 2 , 2 x < 2 , and so 2 ln 2 2 x − 1 < 2 ln 2 ⋅ 2 − 1 = ln 2 − 1 < ln e − 1 = 0 , thus this derivative is negative for all x < 2 and so the function 2 x − x is decreasing for all x < 2 . Also, since 2 x − x = 0 when x = 2 , this establishes that 2 x − x > 0 when x < 2 (if for some x it's negative, it contradicts the fact that it's decreasing). Thus we have proven that 2 x > x for all x < 2 , and plugging x = u i and using Claim 1 gives the result.
Claim 3: { u i } converges.
This follows from Claim 1 and 2. It is increasing but bounded above, thus it converges. So it has a limit L , which from Claim 1 cannot be larger than 2 (otherwise the function doesn't even approach L ).
Claim 4: L = 2 .
This is straightforward. Since u i + 1 = 2 u i , letting i → ∞ gives u i → L , and so L = 2 L . Taking the intermediate result for in Claim 2, we cannot have L < 2 as it would mean 2 L − L > 0 , and we cannot have L > 2 from Claim 3. And since L = 2 satisfies the equation, this is the sought limit.
Thus the answer is 2 .